Implementation Adiwiyata Program in Shaping the Environmental Care Character of Senior High School Students - Komalasari, Ayu; Dewantara, Jagad Aditya; Sulistyarini, Sulistyarini; Arifiyanti, Fitria; Ochieng, Okiri Peter (IJECA (International Journal of Education and Curriculum Application), 2023)
Abstract: The Adiwiyata Program is a government effort to address the crucial issue of environmental preservation, which directly impacts the quality of human life. This research explores student participation in participatory-based environmental activities within the Adiwiyata program. The study was conducted among senior high school students using a case study method with a qualitative approach. Data was collected through interviews and documentation due to the pandemic's limitations on extracurricular activities and online learning. The implementation of the program in senior high schools was carried out through four activity programs: building maintenance, land and facility utilization based on environmental protection and management principles, development of environmentally-focused extracurricular activities, and environmental action activities to commemorate environmental days. The Adiwiyata program has had a positive impact on schools and student behavior, resulting in a clean, beautiful, healthy, and comfortable school environment, increased awareness of environmental cleanliness, and good participation of students in environmental management activities.